Metal-to-Metal Sealing for High Pressure Subsea Production System(SPS) Bolted Flange Connector - Nurul Hidayah Binti Mohammad Radzi, Nurul Hidayah (Universiti Teknologi Petronas, 2009)
Metal to metal seal is one type of static seal used in high pressure Subsea Production System (SPS) Bolted Flange connector. Static sealing elements, as their classification implies, remain stationary relative to the surfaces they are sealing against. The subsea system can be located many miles away in deeper water and tied back to existing host facilities in shallow water. Due to the deeper water, higher challenges and problems need to be considered such as high reservoir pressures, low sea-bed temperatures, large variations in water depth range, flow assurance challenges, geo-hazard issue like gas hydrates, rough metocean condition, remoteness and hydrostatic pressure. The first objective is to analyze how leakages occur in SPS Bolted Flange connector. Bolt, flange and seal are the three main components in Bolted Flange connector that can contribute to the excessive leakage. Once excessive leakage happens in the deepwater, there will be loss in productivity, marine pollution and other important effects that need to be highly considered. From the literature reviews, main factors due to the seal that can cause leakage are inadequate overall flatness, inadequate smoothness and seal ring breakage can be concluded. The second objective is to propose and demonstrate the applicability of metal to metal sealing of SPS Bolted Flange connector for deepwater application. Temperature, pressure, industry design codes, life expectancy, leakage integrity and maintenance and accessibility are the key elements in selection of metal seal for SPS Bolted Flange connector. For this project, metal O-Ring has been chosen as the design for metal seal inside SPS Bolted Flange connector because its characteristics meet the deepwater and subsea requirements. The comparison has been made between Stainless Steel AISI 321, Alloy 600 and Alloy X750 by calculating the pressure exerted on the metal seal. All these materials satisfy subsea requirement but Stainless Steel AISI 321 has been chosen for metal ORing inside Bolted Flange connector due to cost consideration.